A Perspective of the Pore Architecture of Nanoporous Materials by Vapour Adsorption of Aromatics and Olefins - R. Vijayalakshmi Puranik; Prakash Kumar; B.M. Chandrashekara; C. Ravindra Reddy; Y.S. Bhat; B.S. Jaiprakash (Adsorption Science & Technology)
Three nanoporous adsorbent materials, viz. beta zeolite, porous clay hetero-structure (PCH) and hexadecyltrimethylammonium cation-intercalated montmorillonite (Mont-2), having different pore architectures were used in the investigation. The adsorption of benzene, C 1 –C 4 alkyl-substituted benzenes, C 6 –C 9 straight-chain alkenes and isomeric hexenes was studied using a McBain–Bakr gravimetric balance. Interesting observations were made with respect to the adsorption uptake of the different probe molecules for exploring the pore architecture. Beta zeolite is a large pore zeolite (7.5 Å) which allows three-dimensional access to molecules, whereas PCH is known to have large pores allowing two-dimensional access for molecular entry. Irrespective of the number of attached –CH 2 side-chain groups attached, the rate of diffusion of the molecules inside the beta zeolite pore channels was less constrained. However, in the case of Mont-2, where the pores were blocked by the surfactant molecules, adsorption was apparently due to the diffusion of molecules through the interlayer packed with a bilayer of surfactant molecules. The packing density of the adsorbate molecules in the channels of the adsorbent was determined by the space-filling characteristics of the molecules which, in turn, depended on various factors such as the effective molecular volume, steric factors, the positioning of the double bonds, and the attractive and repulsive forces.